Methicillin-Resistant Staphylococcus Aureus in Loja Province, Ecuador - Hof, Sarah (My University, 2012)
Methicillin-resistant Staphylococcus aureus (MRSA) is a strain of Staphylococcus aureus (Sa) which is resistant to methicillin, the antibiotic used most to treat Staphylococcus infections. MRSA poses health risks both in the United States and around the world, and is commonly a hospital acquired infection that results in thousands of deaths annually. Little data is published on MRSA's prevalence in Ecuador and its health impact is poorly understood. In this study, nasal swabs were obtained from individuals in hospitals and rural communities in Loja Province, Ecuador.
Color poster with text, images, and tables.
Keywords: Methicillin resistance--Ecuador--Loja (Province); Staphylococcus aureus infections--Ecuador--Loja (Province); Posters